Evaluation of the In Vitro Wound-Healing Activity and Phytochemical Characterization of Propolis and Honey - Afonso, Alexandra M. (2020)
Honey and propolis are natural substances produced by Apis mellifera that contain flavonoids, phenolic acids, and several other phytochemicals. The aim of this study was to phytochemically characterize three different types of honey and propolis, both separately and mixed, and to evaluate their wound-healing activity. Total phenolic compounds and flavonoids were determined using the Folin–Ciocalteu’s and aluminum chloride colorimetric methods, respectively. The antioxidant activity was evaluated by both the DPPH free radical scavenging assay and β-carotene bleaching test, and the anti-inflammatory activity was determined by a protein denaturation method. To evaluate the wound-healing activity of the samples, NHDF cells were subjected to a wound scratch assay. The obtained results showed that dark-brown honey presents a higher concentration of phenolic compounds and flavonoids, as well as higher antioxidant and anti-inflammatory activities. Propolis samples had the highest concentrations in bioactive compounds. Examining the microscopic images, it was possible to verify that the samples promote cell migration, demonstrating the wound-healing potential of honey and propolis.